The effect of phosphorus supply on white clover (Trifolium repens L.) response to elevated pCO2. I. Symbiotic nitrogen fixation - Almeida, J.P.F. (1998)
Phosphorus is a basic nutrient for plant growth and it becomes determinant of yield and persistence of pasture legumes under conditions of poor and acid soils, a common situation observed in Portugal. P defficiency leads to low nodule mass per plat and lower quantities of symbiotic fixed nitrogen. The nitrogen demand from the plant has an effect over Rhizobium activity. However in low P, Rhizobium activity might be impaired. This situation leads possible to a limitation of white clover growth by phosphorus and nitrogen defficiency.